The effects of pictures on the reading comprehension of low-proficiency Taiwanese English foreign language college students: An action research study - Pan, Yi-Chun; Pan, Yi-Ching (VNU Journal of Foreign Studies; Vol 25 No 3, 2009)
Abstract. This study investigates the extent to which the presence of pictures in text benefits low-proficiency Taiwanese English foreign language (EFL) college students. The findings show that the low-proficiency participants had significantly higher scores on their translation tasks when the text was presented together with the pictures, and that the accompanying pictures facilitated those low-level participants in comprehending not only the simpler but also the more difficult text.  Student responses to the effects of visuals on their reading comprehension also revealed that the pictures enhanced their understanding of the text itself.  Implications are suggested for EFL college teachers, textbook designers, and materials developers.